Constructivist skills and their relationship to kinaesthetic early childhood perception (5-6 years) - Benfadel, Fouad (sports creativity, 2025)
The aim of the research was to highlight the relationship (if any and its nature) between structural motor skills and cognitive sense of mobility of children (5-6) years, and we used the relational descriptive approach, and the sample of the research consisted of 40 children from preparatory education (5-6) years divided into a survey sample estimated at 10 children, and 30 A child for the basic sample, deliberately selected due to the specific age of the age group on the one hand and the availability of parity among the members of the sample on the other, in addition to the availability of material possibilities and administrative facilities. The data and information collection tools were the Hayod cognitive and motor perception test, transitional motor skills tests, control and control skills, as well as fixed and mobile balance skills, and we used SPSS Program to address Data, among the most important findings: -The existence of a strong and statistically significant direct relationship between the various dimensions of cognitive sense and the most structural motor skills in